A Companion to Political Leadership in Central and Eastern Europe after 1990 : Democratization - Political Parties - Elections - Hartliński, Maciej, (Brill's Companions to the Slavic World ;, 2025)
This companion book offers the first comparative publication on political leaders in Central and Eastern Europe after the fall of communism. Through the perspective on leadership, the chapters look analytically at the processes of democratization, the shaping of the party systems and parliamentary elections in the region. Students and scholars will gain a much better understanding of the political developments in the region. Moreover, the work is also helpful to reflect on leadership questions in the context of the stabilized democracies of Western Europe and for other countries still in their institutionalization phase.